Shelf-life prediction and chemical characteristics analysis of milk formula during storage. (June 2021) - Jiang, Yujun; Yang, Xinyan; Jin, Haonan; Feng, Xiaohan; Tian, Fang; Song, Yang; Ren, Yuwei; Man, Chaoxin; Zhang, Wei
Abstract: In this study, changes in the chemical characteristics of milk formula stored at 25 °C, 30 °C and 40 °C during 6 months storage were investigated. Three vitamins degraded to varying degrees at all temperatures with the prolonging of storage time. Lipid oxidation continued to occur during storage. Lipid hydroperoxides content was affected by storage time, while the formation of volatile components was influenced by storage temperature and time. According to the Pearson correlation analysis, propionaldehyde was mainly caused by the degradation of docosahexaenoic acid (C22:6n3, DHA), and hexanal was the primary oxidation product of linoleic acid (C18:2n6, LA) and arachidonic acid (C20:4n6, AA). Fatty acids composition, except polyunsaturated fatty acids (PUFAs), remained stable at all storage temperatures. However, the correlation between PUFAs and volatile components was only shown at 30 °C and 40 °C. Based on the analysis of physicochemical characteristics, the shelf-life of milk formula was predicted by Multivariate Accelerated Shelf-Life Test combined with Arrhenius model. The commercial shelf-life of milk formula was estimated to be stored at 25 °C and 30 °C for 12 and 8 months, respectively. Particle size, vitamin A and color difference could be used as indicators for predicting the shelf-life of dairy products with similar matrices. Highlights: Analyze the chemical characteristics of milk formula stored at 25 °C, 30 °C and 40 °C. The shelf-life of milk formula was evaluated using the MASLT method. The predicted shelf-life of milk formula was 12 months at 25 °C and 8 months at 30 °C. Particle size, vitamin A and ΔE could be used as indicators to predict shelf-life.